One Parameter Family of b-m1 Developable Surfaces of Biharmonic New Type b-Slant Helices according to Bishop Frame in the Sol Space Sol3 - Ergut, Mahmut; Korpinar, Talat; Turhan, Essin (Soc Paranaense Matematica, 2013)
In this paper, we study inextensible flows of b-m(1) developable surfaces of biharmonic new type b-slant helix in the Sol(3). We characterize one parameter family of the b-m(1) developable surfaces in terms of their Bishop curvatures.
Keywords: new type b-slant helix; Sol space; curvatures; b-m(1) developable surface